Understanding each other without crossing the threshold: Martin Heidegger and the Daodejing - Francescato, Sara (Scenari, 2022)
This paper carries out an analysis of Heidegger’s translation of chapter 11 of Daodejing, cited in the essay Die Einzigkeit des Dichters. My purpose is to demonstrate that, although Heidegger uses key terms of his own philosophy to translate the Chinese core concepts of chapter 11, the words he uses share, to some extent, several similarities in meaning with the classical Chinese concepts. In particular, I examine Heidegger’s translation of wu 無, “productive void”, as Leere and his translation of yong 用, “use”, as Sein. Then, I argue that both Heidegger and the Daodejing share a similar perspective on the role of language and on the evocative power of poetry.